2013
DOI: 10.1002/jgrd.50276
|View full text |Cite
|
Sign up to set email alerts
|

Luminosity of initial breakdown in lightning

Abstract: [1] Time correlated high-speed video and electromagnetic data for 15 cloud-to-ground and intracloud lightning flashes reveal bursts of light, bright enough to be seen through intervening cloud, during the initial breakdown (IB) stage and within the first 3 ms after flash initiation. Each sudden increase in luminosity is coincident with a CG type (12 cases) or an IC type (3 cases) IB pulse in fast electric field change records. The E-change data for 217 flashes indicate that all CG and IC flashes have IB pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
244
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(273 citation statements)
references
References 29 publications
(55 reference statements)
26
244
3
Order By: Relevance
“…In several CG flashes, typical downward negative stepped leader developed (after a delay and dark interval of several milliseconds) from near the lower end of the initial leader. Stolzenburg et al [2013a] also showed that each luminosity burst was time correlated with a large-amplitude IBP, whose duration was typically 20-40 μs. Marshall et al [2013] used the array of E-change sensors described in Karunarathne et al [2013] and PBFA locations to study IBPs in IC flashes.…”
Section: 1002/2014jd021553mentioning
confidence: 87%
See 3 more Smart Citations
“…In several CG flashes, typical downward negative stepped leader developed (after a delay and dark interval of several milliseconds) from near the lower end of the initial leader. Stolzenburg et al [2013a] also showed that each luminosity burst was time correlated with a large-amplitude IBP, whose duration was typically 20-40 μs. Marshall et al [2013] used the array of E-change sensors described in Karunarathne et al [2013] and PBFA locations to study IBPs in IC flashes.…”
Section: 1002/2014jd021553mentioning
confidence: 87%
“…Both Stolzenburg et al [2013a] and Karunarathne et al [2013] found that the initial negative leader of CG flashes moves negative charge downward.…”
Section: Overview Of Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Rakov and Uman [3] stated that the PB process can be viewed as a sequence of channels extending in seemingly random directions from the cloud charge source with one of them evolving into the stepped leader propagating to ground. More recent studies of preliminary breakdown by Stolzenburg et al [4,5], who used high-speed video and electric field records, indicated that the PB luminosity bursts were correlated with the PB pulses in the corresponding electric field records and suggested that each PB pulse was caused by a substantial current surge traversing a channel segment of the order of hundreds of meters in length. Nag and Rakov [6], via modeling, estimated the PB pulse peak currents to be of the order of tens of kiloamperes, comparable to or even exceeding the corresponding return-stroke peak current.…”
Section: Introductionmentioning
confidence: 99%